Social impact of abortion’s decriminalization in Portugal - Melo, António (2017)
This paper studies the impact of legalizing abortion in Portugal on fertility and on maternal-infant health indicators, namely on low birth weight (LBW). It used individuallevel data on all pregnancies in Portugal from 2008 to 2014. It retrieved the socio-economic determinants of abortion in Portugal to find that young women, educated, employed, working in low skilled jobs, single, with previous children, without easy access to abortion services and living in conservative regions are more prone to abort. It also found that abortion induces positive selection effects regarding LBWand that it caused a reduction in Portuguese fertility.